The Evolution of Indian Journal of Finance : A Retrospective Review and Future Directions - Ledwani, Sanket; Chakraborty, Suman; Digal, Sabat Kumar (Indian Journal of Finance, 2022)
Indian Journal of Finance (IJF) is one of the most prominent research sources in finance, with a rapidly growing popularity in India and throughout the globe. On the journal’s 15th anniversary (2007 to 2021), this study venerated the journal by providing a detailed retrospective analysis of its output using variate bibliometric tools. Performance analysis revealed a diminishing number of annual publications and growing citations in IJF, illustrating its increasing standards and growing reputation. Bibliographic coupling, content analysis, and thematic review provided the details of various themes that have evolved in the Indian Journal of Finance. The major themes that emerged from papers published in the IJF over the study duration cover: financial inclusion and financial literacy, social and environmental disclosure, stock market efficiency, investor behavior and financial wellbeing, financial crises, corporate governance, volatility, the spillover effect, and capital structure and dividend policy decisions. The journal’s keyword analysis and temporal evolution veraciously showed the recent publication trends and focus of the Indian Journal of Finance. The study discovered the focal areas where most of the papers are published to address contemporary behavioral finance and empirical finance issues covering deep-impact research on the diverse research composition of IJF. We believe that the structural summarization of the published articles will significantly help practitioners espouse corporates’ financial strategies and decisions. It also provided useful future directions to the researchers in all the respective themes for further examination.